Preliminary Analysis Theoretical Basis Of Implementation Of Intensive Fish Farming In Ensuring Food Security - Muydinov Olim Bekmuratovich (Research Parks Publishers, 2023)
This article examines the theoretical basis for the introduction of intensive fish farming to ensure food security. It is scientifically based that the employment of the population is provided through intensive fish farming, as well as the structural changes in the population's diet and lifestyle changes.